Antifungal activity of the volatile oil of Hedyosmum sp., Against species of the genus Candida - María Eugenia Lucena; Katty Latorre N; Francisco Javier Ustáriz Fajardo; Víctor Julio García; Luís Beltrán Rojas Fermín; Adriana Monserrat Monge Moreno; Verónica Paulina Cáceres Manzano (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
The objective of the study was to determine the antifungal activity of the volatile oil of the aerial parts of the plant species Hedyosmum sp., against Candida albicans, C. glabrata, C. tropicalis and C. parapsilosis complex. The plant material was collected from the Jacarón natural forest, Chimborazo Province, Ecuador. The extraction of the essential oil was carried out by hydro-distillation, obtaining a yield of 0.09%. Antifungal activity was studied by means of the diffusion in agar method and the results were interpreted by detection-measurement of inhibition halos and minimum inhibitory concentration. The study was carried out starting from the pure oil and dilutions with dimethyl sulfoxide. The results were validated by positive controls (Fluconazole) and negative controls (dimethyl sulfoxide). The pure oil showed antifungal activity against C. albicans, C. tropicalis, and C. parapsilosis complex, but not against C. glabrata. While, the antifungal activity determined using dilutions of the oil allowed establishing the minimum inhibitory concentration for C. tropicalis, C. parapsilosis complex, at 0,25x106 μg/mL and for C. albicans at 0,5x106 μg/mL. These results concluded that the volatile oil of Hedyosmum sp., Presents little antifungal activity against three of the four Candida species studied